An evaluation of the existing guidance program on the college level of San Nicolas College, Surigao City - Gillo, Arcangelina Custodio (Animo Repository, 1973)
v. 1. This study determines the strengths and weaknesses of thee existing guidance program on the college level of San Nicolas College in Surigao City. The data presented in the study were gathered mainly through observations, personal experiences and reflections of the writer. Materials examined by the author included the organizational flow chart of the school, college guidance office records, registrar's records, teachers' manual, students' handbook, school's brochure, the 1972 Atlas of Surigao del Norte and her lecture notes. She also consulted books, journals, and studies both published and unpublished. The author extensively used the descriptive method of research. Based from the study, the writer found out that the failure of the guidance program in San Nicolas College, Surigao City, was found to be mainly with regard to its objectives. They were not clearly stated there were no specific goals to be realized every year there were suggestions without considering a survey of actual needs of the students. In addition to this, guidance services were found to be highly inadequate, inefficient and not availed of by the students. Since the program had been operating without its own budget, the program was inadequately staffed. Aside from several proposed improvements, she pointed out that there was a need for conducting an in-service training of San Nicolas College of Surigao City. This was to enlighten them about the nature of guidance, to define their role in the program, and to help them see the value of the program in their work. v. 2. This study finds out the correlation between academic performance as shown by the grade six average and the first year academic average, and the intelligence quotient as revealed by the Otis Self-administering Tests of Mental Ability of the San Nicolas College (SNC) high school freshmen for the school year 1971-72. Specifically, it attempts to determine the validity of the grade six average as basis for sectioning the high school freshmen, to discover which of the variables is the best predictor of academic performance in the first year high school, and to find out the coefficient/percentage of forecasting efficiency or of dependability of the paired variables. The group used in this study is composed of 190 high school freshmen of SNC for school year 1971-72. Their ages range from 11 to 19 years, with the mean age of 12.81 years. Sixty-three percent (119 students) of the population are females and thirty-seven percent (71 students) are males. Eighty-two percent (155 students) finished elementary grades from the public schools and only 18 percent (35 freshmen) from private schools. Eighty-two percent (29 freshmen) of those of came from the private schools were products of the SNC elementary department. Findings show that the first year academic average correlated highly and positively with the Otis I.Q. (.71) and with the grade six average (.71), all significant beyond the .01 level. However, the Otis I.Q. related moderately but still substantially and positively (.67) with the grade six average, still significant beyond the .01 level. Hence, the null hypothesis is rejected and the hypothesis that there is a significant correlation between the first year academic average and the Otis I.Q., between the first year academic average and the grade six average, between the Otis I.Q. and the grade six average is accepted. Also, the results reveal the validity of the grade six average as basis for sectioning the high school freshmen. Moreover, they point out that the combined use of the two predictors : Otis I.Q.